REVIEW OF POTENTIAL PLANTS IN INDONESIA AS AN ANTIDIABETIC WITH HYPOGLYCEMIC ACTIVITIES - Hanggaresty, Mutiarani Dasha; Warditiani, Ni Kadek (Journal Pharmaceutical Science and Application; Vol 3 No 2 (2021): Journal Pharmaceutical Science and Application, 2021)
Background: Diabetes mellitus which is characterized by hyperglycemia is a metabolic disease due to insulin action, defects in insulin secretion, or both. Various studies have shown that herbs that have a hypoglycemic effect can be used in the treatment of diabetes mellitus. Generally, herbs can slow down the complications of diabetes mellitus and improve metabolism. The ability of plants to restore the function of pancreatic tissue to increase insulin production or make it easier for insulin to process glucose is related to the effects of hypoglycemia. Objective: Comparing plants that have a hypoglycemic activity that can be used in the treatment of diabetes mellitus in Indonesia. Methods: studying literature from various databases, websites, national journals, and relevant international journals to identify plants that have hypoglycemic activity. Results: The mechanism A. sativum as a hypoglycemic involves different fiber viscosities; A. vera involved as a hypoglycemic by protecting pancreatic? cells; Asiatic acid in C. asiatica increasing glycolysis by restoring the activity of key enzymes; G. max inhibiting ?-amylase and the stigmasterol increasing the absorption of blood glucose and reducing insulin resistance; P. macrocarpa exert their antidiabetic action via ?-glucosidase modulation, an extra distinctive pancreatic mechanism; S. arvensis has the potential to inhibit ?-amylase enzymes. Conclusions: This review article has presented 6 detailed comparisons of plants that have a hypoglycemic activity that can be used in the treatment of diabetes mellitus in Indonesia and we believe can be useful for students, researchers, or practitioners. Keywords: Diabetes mellitus, hypoglycemia, Indonesian plants